Internet connectivity disruption in LS (Lesotho) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Lesotho. Data sourced from IODA.
Network Disruption Incident ID: LS-2026-0003. Severity: critical. Confidence: 65%